FRI0146 Proof of Concept: Objective Assessment of Physical Function with the Instrumented Bath Ankylosing Spondylitis Functional Index (IBASFI). (10th June 2014) - Swinnen, T.; Milosevic, M.M.; Van Huffel, S.; Dankaerts, W.; Westhovens, R.; de Vlam, K.
Abstract : Background: To date, the established method to assess physical function in patients with axial spondyloarthritis is the self-reported Bath Ankylosing Spondylitis Functional Index (BASFI). In an attempt to overcome the shortcomings of self-reported outcomes such as recall bias and aberrant self-judgments, performance-based assessment of physical function has become increasingly popular in the field of axial spondyloarthritis 1 . We developed reliable and valid algorithms to automatically detect movement time during performance-based tests using on body-worn sensor that need to be compared to the established BASFI. Objectives: To compare automated movement time detection to each corresponding Bath Ankylosing Spondylitis Functional Index (BASFI) item (i.e. construct validity). To reduce the number of performance-based tests to assess physical function in patients with axial spondyloarthritis. Methods: Twenty-eight consecutively evaluated patients with axial spondyloarthritis (Age: 43.69 (10.45); BMI: 26.19 (5.71); BASMI: 3.11 (1.60); BASFI: 3.41 (2.19); sex: 16M, 12F) completed twelve (10 with movement time, 1 with height and 1 with range of motion as the outcome of interest) performance-based tests derived from the BASFI questionnaire. All patients wore a two-axial accelerometer fixed on the upper arm or the trunk. A blinded physical therapist guided the tests and the BASFI and all other clinical data were collected up front. Movement time was extracted from filtered accelerometer signals using custom-written automated algorithms in MatLab. Prior work established the reliability of this method (ICC range 0.753 to 0.986). Each performance-based test was related for construct validity purposes to the corresponding BASFI item and total BASFI score using Pearson-product moment correlation coefficients. A stepwise linear regression was used to model the BASFI from an optimal set of performance-based tests. Results: Good to excellent construct validity for each instrumented performance-based test was found with overall significant and moderate to good association with the corresponding BASFI scale (rs) or item (ri) for sock test (rs 0.376, ri 0.466), pen test (rs 0.482, ri 0.480), 5 pens speed test (rs 0.597, ri 0.402), maximal reach test (rs -0.374, ri -0.230), shoulder speed test (rs 0.300, ri 0.397), sit-to-stand test (rs 0.631, ri 0.706), getting up test (rs 0.488, ri 0.462), stair climbing test (rs 0.617, ri 0.546) and looking over the shoulder test (rs 0.520, ri 0.730). Together, sit-to-stand speed test (standardised Beta: 0.464, p: 0.003), looking over the shoulder test (standardised Beta: -0.362, p: 0.015) and maximal reach test standardised Beta: -0.325, p: 0.019) explained 55% of the variance in BASFI, confirming construct validity of the composite and successful reduction of items. No issues on collinearity were detected with the variance inflation factor and tolerance statistics. Conclusions: The novel performance-based iBASFI showed excellent construct validity and is suitable for clinical use. The number of performance-based tests needed to model physical function can be minimized without compromising validity. References: van Weely SF, et al. Rheumatology (Oxford). 2009 Oct;48(10):1254-60. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.6047